Strategy and policy statements on green ICT : an Islamic perspective. - Hameed, Shihab A. (IIUM Press, 2011)
In this information and knowledge era; ICT development and industry are growing very fast and associated with huge procurement force. Today, the global society is facing serious challenges in improving environmental performance, particularly with climate change, global warming, and resource management. ICT industry is widely contributing to the global economy associating with innovation, invention and rapid development of almost all the aspect of human life. On other hand; ICT industry is responsible for global CO2 emissions. Global environmental problems are affecting directly many countries’ energy and industrial policies. The rapid increasing of ICT usage means more energy consumption and more environmental problems and the estimated ICT consumption of energy will be about 15% of the total consumption worldwide in 2020. Therefore, many countries are establishing Green ICT policies which increase energy efficiency due to correspondence climate change. Therefore, governments especially in developing and Islamic countries need to adopt new strategic policies for efficient energy use in ICT. This study presents the current environmental problems related to green ICT and the efforts to solve it. Several studies have warning from the current energy consumption paradigm, based on newly changed ICT practices. This study provides guidelines for decision makers and ICT professionals to enhance their work toward green ICT and eliminating environmental problems. Islamic viewpoint on environment and its protection is considered since it offers comprehensive, stable, and fair viewpoint that is based on main Islamic sources; Qur‘an and Sunnah. Hundreds of Qur‘anic verses and prophet Hadiths clarify (directly or indirectly) the right manner in dealing and protection of environment resources. This paper proposes a framework for strategy and policy statements of green ICT based on Islamic perspective to serve the world especially developing and Islamic countries.